Epigraphic Stable Formulae: Manifestations of the Phenomenon in the Context of the Written Heritage of the Armenian Highlands - Harutyunyan, Arsen; Sargsyan, Vahe; Gyulamiryan, Hayk (Revista Arheologică, 2026)
The epigraphic culture of the Armenian Highlands is noteworthy for its distinctive manifestations, among which the structure of the text stands out with a number of specific features. The phenomenon becomes especially intriguing when studied diachronically, through a comparison of pre-Christian and Christian written heritage. A comprehensive study of stable epigraphic formulae – examined here for the first time on the basis of the cuneiform inscriptions of the Kingdom of Van, the Aramaic inscriptions of Classical Armenia, and Armenian medieval epigraphic inscriptions – reveals that the tradition of composing inscriptions in the Armenian Highlands follows a unified canonical system. Within this system, the introductory, occasion-event, purpose-expectation, and concluding (curse-blessing) formulae of the text are clearly distinguished.
Keywords: epigraphic inscription; cuneiform inscription; Aramaic inscription; stable formulae; structure; titulary; motive; purpose; expectation; curse; blessing